Naloxone Plus, Plus Some: Examining Ohio's Quick Response Teams Through the Lens of Deflection. Issue 6 (November 2022) - Firesheets, Kelly; Juarez, Sophia; Kopak, Albert; Ross, Jon; Sperber, Kimberly; Reichert, Jessica
Abstract : There were nearly 50 000 opioid-related deaths in 2019 in the United States.* The dramatic frequency of opioid overdoses and fatalities has led to strained community resources, especially among hospitals and first responders (law enforcement, fire, and emergency medical services). In response to rising overdose rates, many first responders have implemented programs that align public health and public safety responses to overdoses. Often called "Quick Response Teams" (QRTs), these programs leverage a collaborative team to respond to those at risk of overdose, or who have survived an overdose. The initial QRT was implemented in Colerain Township, Ohio, in 2015.† Today, QRTs are a widely accepted "model" overdose response program.‡ Despite the popularity of QRTs, research on the model is limited. In this article, the authors use existing qualitative and quantitative data from QRTs across the state of Ohio to examine QRTs. Using the lens of the Police, Treatment and Community Collaborative's 5 deflection pathways, the authors answer four key questions: (1) What is the scale of QRTs in Ohio, and how are QRTs in our sample structured? (2) Whom are the QRTs serving? (3) How many pathways of deflection are reflected in Ohio's QRTs? (4) What can these data teach us about the context of the QRT work and (more generally) collaborative overdose response? After examining the QRTs and their data, the authors provide suggestions to help researchers, practitioners, and funders better understand QRTs and similar public health/public safety partnerships.